What Were Thomas Hearne's 'Bad Copies'?. (8th September 2021) - Day, Geoffrey; Junqua, Amélie
Abstract: Bodleian, MS Rawl. Q. e. 18 is a twelve-page notebook in which Thomas Hearne recorded income and expenditure relating to his publication of Thomas Caius' Vindiciae antiquitatis academiae Oxoniensis (1730), together with very brief details of the instructions given to the printer about five other texts. For five of the six titles Hearne specified that, in addition to the numbers required for subscribers, there should be an additional two 'bad copies'. This note explores possible interpretations of this instruction.